Growth responses of tropical forage plant species to vesicular- arbuscular mycorrhizae. 1. Growth, mineral uptake and mycorrhizal dependency - Saif, SR (Springer, 1987)
Growth and mineral uptake of twenty-four tropical forage legumes and grasses were compared under glasshouse conditions in a sterile low P oxisol, one part inoculated and the other not inoculated with mycorrhizal fungi. Shoot and root dry weights and total uptake of P, N, K, Ca, and Mg of all the test plants were significantly increased by mycorrhizal inoculation. Mycorrhizal inoculation, with few exceptions, decreased the root/shoot ratio. Non-mycorrhizal plants contained always lower quantities of mineral elements than mycorrhizal plants. Plant species showed differences in percentage mycorrhizal root length and there was no correlation between percentage mycorrhizal infection and plant growth parameters. A great variation in dependence on mycorrhiza was observed among forage species. Total uptake of all elements by non-mycorrhizal legumes and uptake of P, N and K by non-mycorrhizal grasses correlated inversely with mycorrhizal dependency. Mycorrhizal plants of all species used significantly greater quantities of soil P than the nonmycorrhizal plants. Utilization of soil P by non-mycorrhizal plants was correlated inversely with mycorrhizal dependency.